Automatización de la estación mecatrónica de verificación Prüfen (2019)
The PSV station, is one of the six mechatronic units the SENA has, which elements, such as an acting element series, sensors and indicators that manipulate device pieces, identify their characteristics and the nature of them. The present document states some alternatives to automate the PSV station, in addition, it explains the development of one of these methodologies, “Programmed Logic Strategy”, in order to give solution to the outlined problem.